PENGARUH MEDIA PEMBELAJARAN MOTION GRAPHIC DALAM MENINGKATKAN RESPON SISWA PADA MATERI INFLASI DI SMA NEGERI 12 MEDAN - David Cristian Silitonga; Irna Della Br Ginting; Nataline Simanjuntak; Suryani Br Ginting; Yulce Ketrina Karubui; Evi Syuriani Harahap (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of motion graphic learning media in improving student responses to inflation material at SMA Negeri 12 Medan. This study employed a quantitative approach using simple linear regression analysis to determine the relationship and influence between motion graphic learning media and student responses. The research sample consisted of 35 students selected as respondents. Data collection was conducted through questionnaires that had previously been tested for validity and reliability using IBM SPSS Statistics. The results showed that the research instruments met the validity and reliability requirements, with Cronbach’s Alpha values of 0.893 for the motion graphic learning media variable and 0.880 for the student response variable. The Pearson correlation test indicated a strong positive relationship between motion graphic learning media and student responses, with a correlation value of 0.771 and a significance level of 0.000. Simple linear regression analysis revealed that motion graphic learning media contributed 59.4% to the improvement of student responses, while the remaining percentage was influenced by other factors outside this study. The hypothesis testing results showed that the t-value of 6.944 was greater than the t-table value of 2.034 with a significance value of 0.000 < 0.05, indicating that the research hypothesis was accepted. The increased use of motion graphic learning media has proven to have a positive and significant effect on student responses to inflation material at SMA Negeri 12 Medan. The use of motion graphic learning media is capable of increasing students’ interest, attention, participation, and engagement during the learning process, thereby creating a more effective and interactive learning environment.